A BI-LEVEL PROGRAMMING MODEL FOR SERU ORDER ACCEPTANCE AND SCHEDULING PROBLEM CONSIDERING WORKER ASSIGNMENT - Wang, Lili; Zhang, Zhe; Yin, Yong (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
As an innovative and successful manufacturing mode in Japanese production practice, seru production has attracted extensive attention due to its high efficiency, high flexibility, and quick responsiveness. This paper focuses on the order acceptance and scheduling problem in seru production system considering worker assignment simultaneously, where the worker’s learning curve effect is also concerned because it is also an important issue for the stable performance of the entire production system. A bi-level programming model is built where the worker assignment on the upper level is to maximize worker’s skill proficiency increments, while the lower level is to maximize the total net revenue by finding out the optimal order acceptance results and scheduling plan. Then, a bi-level nesting genetic algorithm (BNGA) is developed according to the natural structure of proposed mathematical model. Finally, a numerical example is applied to illustrate the feasibility and validity of the bi-level model and BNGA.